Ectoparasitos de morcegos em área de restinga, Sergipe: uma análise ecológica e filogenética - Bezerra, Rayanna Hellem Santos (2018)
The structuring of the bat parasite community can be influenced by the seasonality, body size, sex, geographical distribution and evolutionary history of the host. This study aimed to characterize the community of ectoparasites associated with bats in the restinga area, Sergipe; as well as to present the parasitological descriptors and the association of the parasitism with the body size and sex of the host. Field campaigns were held monthly for two consecutive nights between October 2016 and September 2017. For the capture of bats, 10 mist nets were placed inside the restinga and the collected ectoparasites were stored in 70% alcohol. For the parasitized bats the parasitological rates and the index of specificity were obtained and the infracommunities were recorded. The influence of host body size on the richness and abundance of ectoparasites through linear regression was evaluated. For the most abundant ectoparasites, the influence of the sex of the host on the prevalence rate was verified through the chi-square test and the mean intensity through the t-test. For the influence of seasonality on the same rates GLM was performed. The relationship between the geographic extent of host occurrence and the richness of ectoparasites was evaluated by means of linear regression. In order to verify if phylogenetically closest hosts shared parasites, a Mantel test was performed. The parasitized bats belong to the families Phyllostomidae (N = 163; S = 11) and Vespertilionidae (N = 3; S = 2). The ectoparasites correspond to the families Spinturnicidae (N = 131; S = 1), Argasidae (N = 30; S = 2), Nycteribiidae (N = 9; S = 2) and Streblidae (N = 260; S = 13). The most abundant ectoparasites were Periglischrus iheringi and Trichobius joblingi. The registered infracommunities are composed by species of different genera. There was no influence of host body size on parasitism, which may be associated with the similarity between host body mass. The influence of the sex of the host on the prevalence rate between Artibeus lituratus and P. iheringi, being the most parasitized females, can be explained by their higher susceptibility to parasitism due to the longer stay in the shelters. Regarding seasonality, differences in prevalence rates and mean intensity were observed for the association between Carollia perspicillata and T. joblingi, with higher values during the season with lower temperature. This influence may be due to biological differences between parasite species. It was possible to observe an increase in the richness of ectoparasites with the increase of the geographical extension of the host, which can be explained by the fact that hosts with a wide distribution are more likely to encounter the parasites. There was no relation between the phylogenetic proximity of the hosts and the sharing of parasites, being able to be related to the different biogeographic patterns of the areas. This study presents important information related to the host-parasite interaction, especially for Sergipe, highlighting the need for more analysis involving the theme in order to better understand the factors that shape this relationship.